Nano-manipulation and nano-assembling using shape memory alloy nanogripper of metal oxide and semiconductor single nanowires and nanoparticles for biological nanosensors - Koledov, Victor (Animo Repository, 2019)
The nanomaterials based on metal oxides or semiconductor nanoparticles and nanowires appear to demonstrate the unique physical and also functional properties. Those properties, in general, allow constructing a large number of individual nanodevices for promising applications in nanoelectronics, photonics and biomedical technology. Such individual nanodevices represent interesting building blocks for new type of hierarchical mechanical nano-assembling. Mechanical hierarchical nano-assembly of functional nanoscale/meso-macroscale devices into macroscopic devices opens up the new perspectives for the creating of micro-meso and macrodevices and their arrays for many applications. The report describes the physical principle and design of the shape memory based nanogrippers as well as the preliminary results of the manipulation of CNTs, InP, ZnO nanowires and nanoparticles as building blocks for biomedical sensors. © 2019 Vietnam Academy of Science & Technology.